Measuring the effective implementation of the GEQIP reform at school level in Ethiopia - Eryilmaz, Nurullah (Frontiers in Education, 2024)
This study examines the substantive impact of educational reforms on school and classroom organization worldwide, noting that many reforms have been more rhetorical than practical in enhancing educational quality. It highlights the crucial role of school principals in driving changes to improve student learning, despite the challenges of implementing reforms that have historically not led to significant increases in student achievement. Focusing on the General Education Quality Improvement Programme (GEQIP) in Ethiopia as a case study, this research aims to assess the extent of reform implementation across schools by identifying variations in the level of implementation. Through a quantitative approach using school principal surveys, the study employs a range of methodological strategies—including principal component analysis (PCA), confirmatory factor analysis (CFA), hierarchical cluster analysis, and K-means cluster analysis—to develop scales and indicators that classify schools into high or low categories of policy implementation. The findings reveal a partial and uneven implementation of GEQIP across Ethiopian schools, with notable disparities in reform adoption levels. This paper concludes by discussing the effectiveness of the methodologies used to categorize schools based on reform implementation and the implications of these findings for the successful execution of educational reforms in Ethiopia and similarly situated contexts. The study underscores the necessity of devising targeted strategies to assist principals and schools in fully achieving the goals of educational reforms.